2019
DOI: 10.1002/ijc.32235
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment outcome of pembrolizumab in patients with nonsmall cell lung cancer and chronic obstructive pulmonary disease

Abstract: Emerging immune profiling data suggest a higher sensitivity to immune checkpoint inhibitors (ICIs) in nonsmall cell lung cancer (NSCLC) patients with chronic obstructive pulmonary disease (COPD), compared to those without COPD. This study aimed to investigate the clinical impact of COPD on the treatment response to ICIs in a large number of patients with NSCLC. In total, 133 patients with spirometry test results were retrospectively identified among those who received palliative pembrolizumab for NSCLC. COPD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…In the present study of patients with advanced-stage lung cancer who received ICI therapy, the presence of COPD was significantly associated with longer PFS, which is in accordance with previous studies (9,22,23). The subgroup analysis revealed that moderate and severe COPD tended to have a better impact on the survival of these patients, though these differences did not reach significance.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study of patients with advanced-stage lung cancer who received ICI therapy, the presence of COPD was significantly associated with longer PFS, which is in accordance with previous studies (9,22,23). The subgroup analysis revealed that moderate and severe COPD tended to have a better impact on the survival of these patients, though these differences did not reach significance.…”
Section: Discussionsupporting
confidence: 90%
“…With rapid advancement in immune-oncology, immune checkpoint inhibitors (ICIs) have shown promising results and are now considered as standard of care in advanced NSCLC 31,32. In particular, the presence of COPD is associated with better survival outcomes in patients with advanced NSCLC treated with ICIs 33. Of note, recent studies demonstrated that combining immunotherapy and radiotherapy may improve the outcome of oligometastatic or advanced lung cancer with tolerable side effects 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that current or former smokers with NSCLC are more likely to respond to ICI therapy (2,3). Recently, it was reported that the presence of COPD was associated with longer progression-free survival (PFS) in patients with NSCLC treated with ICIs (11)(12)(13).…”
mentioning
confidence: 99%